Retrospective characterisation of solitary cutaneous histiocytoma with lymph node metastasis in eight dogs. (3rd August 2016) - Faller, M.; Lamm, C.; Affolter, V. K.; Valerius, K.; Schwartz, S.; Moore, P. F.
Abstract : OBJECTIVES: To describe a small subset of canine solitary cutaneous histiocytoma in which lymph node metastasis has been documented. METHODS: Cases of dogs with solitary cutaneous histiocytoma lesions and regional lymph node metastasis diagnosed via histopathology were found through a retrospective search of the databases of IDEXX Laboratories and the University of California, Davis Veterinary Medical Teaching Hospital Clinical Diagnostic Laboratories. Information on signalment, history and clinical follow‐up was obtained from the submittal form and/or via a questionnaire to the submitting veterinarian. Slides were available for review in seven cases and when possible immunohistochemistry was reviewed or performed by a single pathologist. RESULTS: Eight cases met the inclusion criteria. The neoplasms had the typical appearance of histiocytomas. All tested samples were immunoreactive for CD18 and lacked immunoreactivity for other lymphocyte markers and CD11d. Immunoreactivity for E‐cadherin varied among the neoplasms tested. Outcome was known for five dogs and at the time of manuscript preparation three of those dogs were alive 1682 days, 570 days and 318 days post‐diagnosis. Of the other two dogs with known outcome, one was euthanased shortly after diagnosis and another was hit by a car. Of the dogs that were eventually lost to follow‐up, one was reported to be disease‐free 1003 days after diagnosis. CLINICAL SIGNIFICANCE: Metastatic histiocytoma is rarely reported and distinction from aggressive disease processes such as histiocytic sarcoma may be difficult. Based upon a small number of cases with known outcomes, some dogs with solitary metastatic histiocytoma may experience favourable outcomes.